2022
DOI: 10.3390/pharmacy10010026
|View full text |Cite
|
Sign up to set email alerts
|

Career Preference and Factors Influencing Career Choice among Undergraduate Pharmacy Students at University of Khartoum, Sudan

Abstract: The pharmacy profession has expanded and adapted to changes in community needs. Although career planning and understanding the determinants of career choice are essential, there remains a lack of studies exploring factors influencing future career plans. This study was conducted to identify career preferences and factors influencing future career choices among undergraduate pharmacy students. A cross-sectional study was carried out at the Faculty of Pharmacy, University of Khartoum. A self-administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…The present multiinstitutional study showed that clinical pharmacy was the most common pathway chosen by pharmacy interns and that the choice was mostly influenced by internship training. A similar finding was reported in a study from Sudan, where the clinical pharmacy was ranked the top selected career path (30% of 220 survey respondents), which was influenced by previous training experience (80%) [10]. Interestingly, the study also found that curriculum content was another major influencing factor (70%) unlike our study that found that such factor had an impact on career choice of only 17.8% of the participants.…”
Section: Discussionsupporting
confidence: 89%
“…The present multiinstitutional study showed that clinical pharmacy was the most common pathway chosen by pharmacy interns and that the choice was mostly influenced by internship training. A similar finding was reported in a study from Sudan, where the clinical pharmacy was ranked the top selected career path (30% of 220 survey respondents), which was influenced by previous training experience (80%) [10]. Interestingly, the study also found that curriculum content was another major influencing factor (70%) unlike our study that found that such factor had an impact on career choice of only 17.8% of the participants.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are quite unique with some similarities and differences to previous studies [ 35 , 36 , 37 , 38 ]. For instance, Arhab et al (2022) who recruited Sudanese undergraduate pharmacy students with a very high female-to-male ratio (86%:14%), reported clinical pharmacy practice, academia and research and work in the pharmaceutical industry as their first, second and third career preferences, respectively [ 28 ]. Their findings differ from this current study when the entire study population (male and female respondents together) are compared with theirs.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using a structured self-administered questionnaire that was developed with inspiration from previous studies with credible methodological approaches [ 2 , 28 ]. The questionnaire consisted of five main parts: A, B, C, D and E. The first part took an inventory of the sociodemographic characteristics of the students including gender, age, level of study and source of funding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents denied the impact of family members on their career choice in a study conducted by (Suan, Mat and Im, 2012). A study was conducted by Ahmed et al (2022) to identify career preferences and factors influencing future career choices among undergraduate pharmacy students. A cross-sectional study was carried out at the Faculty of Pharmacy, University of Khartoum.…”
Section: Review Of Literaturementioning
confidence: 99%